Study Pemilihan Supplier Produk Ikan Cupang Hias Dengan Metode Analitycal Hierarki Process (Study Kasus Pada Toko Independent Betta Metro) - Rafi, Galeh Nurly; Yateno, Yateno (Jurnal Manajemen DIVERSIFIKASI, 2022)
Supplier selection is one important thing for companies in purchasing activities. Supplier selection is a multi-criteria problem which includes quantitative and qualitative factors. One method that can be used to select supplier is AHP (Analytical Hierarchy Process) method, which will develop partnership relationships with Betta fish suppliers. The problems that will be discussed in this study are : (1) How to determine the order of priority criteria and subcriteria to make the best supplier selection according to the condition of the company? (2) How to make the best supplier selection according to the conditions and capabilities of the company? The samples to be taken in conducting this research are decision makers and parties who know the supplier’s performance. The sampling technique uses Judgment sampling because the AHP method reqires dependence on a group of experts on the types of specialists involved in decision making. This study uses the AHP method and is assisted by MS Exel, from the assessment of the level of importance of the criteria in selecting suppliers to produce the priority scale/weight as follows: priority I quality (0,440), priority II price (0,226), priority III shipping (0,142), priority IV service (0,099), priority V payment (0,091). From the results of the assessment of the level of alternative importance in the selection of suppliers produces the priority scale/weighting as follows: priority I dedi betta (0,451), priority II rudi bocor (0,348), priority III supplier of niko surya (0,199). Based on the results of the above analysis, the advice that can be given is, if the company will develop partnership relationships with suppliers, the company is prioritized for choosing dedi betta as bettafish suppliers in the company, because dedi betta supplier has the highest overall value. With the existence of this partnership, the supply chain performance between suppliers and companies will be better and can facilitate the overall production completion target. Keywords : Supplier selection, Analytical Hierarchy Process (AHP), best supplier.